2020
DOI: 10.20411/pai.v5i1.388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Six Weekly Oral Fecal Microbiota Transplants in People with HIV

Abstract: Background: Reduced microbiota diversity (dysbiosis) in people with HIV (PWH) likely contributes to inflammation, a driver of morbidity and mortality. We aimed to evaluate the safety and tolerability of 6 weekly oral fecal microbiota transplants (FMT) administered to reverse this dysbiosis.Methods: Six PWH on suppressive antiretroviral therapy (ART) received 6 weekly doses of lyophilized fecal microbiota product from healthy donors. Shotgun sequencing on stool before, after last FMT, and 20 weeks thereafter wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Multiple doses of oral FMT also showed improvement in symptoms during 48 weeks of follow-up, compared to previous supplements [ 25 ]. Utay et al [ 24 ] also reported the safety and tolerability of repeated doses of oral FMT. However, they did not explain the required dose or duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple doses of oral FMT also showed improvement in symptoms during 48 weeks of follow-up, compared to previous supplements [ 25 ]. Utay et al [ 24 ] also reported the safety and tolerability of repeated doses of oral FMT. However, they did not explain the required dose or duration.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not explain the required dose or duration. The small number of study participants limits the dependence on the results [ 24 ]. The study by Garcia-Garcia-de-Paredes et al reported the resolution of diarrhea in 87% of patients with Clostridium difficile infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another smaller study, which involved weekly FMT in six people living with HIV, demonstrated increased gut microbial diversity over a 6-week treatment period. One participant in this study also experienced an improvement in biomarkers of gut permeability and inflammation [ 152 ]. Moreover, FMT in chickens improved resistance against the avian influenza virus [ 118 ].…”
Section: Microbiome-based Therapies In Viral Infectionsmentioning
confidence: 99%
“…Current evidence supports investigating therapeutic strategies for immune modulation in HIV. However, so far, no intervention targeting the microbiota of PLWH either by using prebiotics ( 16 , 16 , 60 ), probiotics ( 61 63 ), synbiotics ( 64 ), rifaximin ( 65 , 66 ), or even fecal microbiota transplants ( 67 , 68 ) have convincingly proved to effectively temper inflammation or enhance boost immune recovery following ART initiation. In general, there was lack of standardization in the outcomes assessed (ranging from studies designed to assess T cell changes ( 60 , 64 ) to exploratory studies evaluating multiple markers of T cell activation ( 69 ) or soluble markers of inflammation or bacterial translocation), the duration of the intervention (from weeks ( 16 , 61 , 62 , 69 ) up to one year), the disease status (from ART naive patients followed without ART ( 60 ) or patients presenting at advanced stages of the disease ( 64 ) starting ART to patients under ART-mediated HIV RNA suppression ( 61 63 ), and even the dosage and components of the prebiotic or probiotic mixtures ( 16 , 62 64 , 69 ).…”
Section: Influence Of the Microbiota On Hiv And Hpv Infectionsmentioning
confidence: 99%